The role of Primary Health Care in assisting pregnant women with toxoplasmosis and children with congenital toxoplasmosis: an integrative literature review (Research, Society and Development, 2023)
Objective: to understand the role of primary health care in assisting pregnant women with toxoplasmosis and children with congenital toxoplasmosis. Methodology: Integrative literature review, operationalized in PUBMED, LILACS, CVSP, MEDLINE, BDEnf and IBECS databases, and CAPES journals related to the subject. Results: A sample of six articles was obtained, selected among the complete articles, in Portuguese or English, published in the last ten years, with observational methodology, and that had greater thematic relevance to the proposed objective. Final considerations: the role and importance of PHC in the control, diagnosis and treatment of toxoplasmosis is emphasized, especially in relation to health education with the theme also involving congenital toxoplasmosis, secondary prevention with early diagnosis of toxoplasmosis during pregnancy and treatment when cases are identified.